Analisis Manajemen Persediaan Dengan Metode Economic Order Quantity (EOQ) Pada Persediaan Bahan Baku UKM Bydevina - Delia Adni Prihasti; Arie Apriadi Nugraha (Indonesian Accounting Literacy Journal, 2021)
UKM Bydevina is an online-based home industry that focuses on hijab and muslim clothing. However, the company has not implemented proper inventory management in running the business. The order quantity of raw materials is only based on estimaste and there is no inventory costs calculation. This study aims to determine UKM Bydevina’s policy in managing raw material inventory, managing raw material inventory using the EOQ method and comparing inventory costs before and after applying the EOQ method. A descriptive-quantitative method is employed in this research. The data was collected thorugh documentation, interview and observation. The result shows that the EOQ for Diamond Fabric is 2.731 yards/order, Moscrepe Fabric is 2.581 yards/order, Rayon Fabric is 763 yards/order and Bubble Pop Fabric is 1.978 yards/order. Then, the company can save inventory costs for Diamond Fabric by Rp 2.102.678 or 12,2%, Moscrepe Fabric by Rp 1.266.937 or 9,6%, Rayon Fabric by Rp 394.052 or 6,2% and Bubble Pop Fabric by Rp 372.426 or 5,3%.